Patenting biotechnical innovation eligibility, ethics and public interest - Hawkins, Naomi 1980- (Edward Elgar Publishing, 2022)
This book examines patent law and policy in biotechnology across the full lifecycle of the patent, focusing on the patent bargain and the public interest. It considers the central issues of how to strike an effective balance of rights, and whether public interest is adequately safeguarded - two issues that are particularly important in areas of rapidly emerging technology. Expert contributors are brought together to explore patent eligibility in biotechnology, focusing on the fields of precision medicine, biofabrication and non-invasive prenatal testing. Chapters also explore the construction and coherence of exceptions to patentability,an examination of FRAND licensing in the context of the internet of medical things, and the possibility of using licensing to encourage or ensure the ethical use of patented technologies. With its carefully constructed analysis, this book will be an excellent resource for academic researchers, and students, in the fields of biotechnology law, pharmaceutical law and intellectual property law. It will also be useful for legal practitioners and policymakers, as well as charitable bodies and non-governmental organisations"--